Consideration of diaphragm flexibility in the seismic design of one-story buildings. (15th November 2016) - Mortazavi, Pedram; Humar, Jagmohan
Highlights: Seismic response of one-story buildings with a flexible diaphragm is studied. Equations for the design of buildings with flexible diaphragm are provided. Equations for predicting the increase in diaphragm internal forces are provided. Diaphragm as the main energy dissipating system is studied. Empirical expressions for the design of an inelastic diaphragm are suggested. Abstract: The response of single-story buildings with a flexible roof diaphragm to earthquake excitations is strongly influenced by the flexibility of the diaphragm. Diaphragm flexibility increases the period of the building, magnifies the ductility demand on the lateral load resisting system, and changes the manner in which the inertia forces are distributed along the length of the diaphragm, which leads to a magnification of the internal forces in the diaphragm. An analytical study is carried out to examine the influences of diaphragm flexibility on the seismic response of one-story buildings. The magnification in bending moment and shear force is investigated. An alternative approach to the seismic design of one-story buildings with flexible diaphragms is studied. In such approach, the diaphragm is designed to act as the energy dissipating system while the braces are designed to remain elastic. The effects of the nonlinearity of the diaphragm on the seismic response of the system are examined and methods are proposed to account for the structural implications associated with designing the diaphragm to act as the energy dissipating system.